A Global History of Execution and the Criminal Corpse
XVI, 313 p. 7 illus.
Keywords: The chapters 'Introduction: A Global History of Execution and the Criminal Corpse' and 'The Gibbet in the Landscape: Locating the Criminal Corpse in Mid-Eighteenth-Century England' are open access under a CC BY 4.0 license.